2018
DOI: 10.5539/jel.v7n5p1
|View full text |Cite
|
Sign up to set email alerts
|

Effective Groupwork Strategies: Faculty and Students’ Perspectives

Abstract: The goal of this research study was to find what makes groupwork to be successful. We asked faculty why they give groupwork assignments to their students and what their opinions about the best practices in creating effective groupwork environment for their students are. It was also intended to compare instructors’ opinions with research findings to find out how much their groupwork strategies match research findings in this area. Likewise, we asked students about features of successful groupwork to see if facu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 18 publications
(23 reference statements)
0
22
0
Order By: Relevance
“…In situations where there is a shorter amount of time available to complete a group task, such as an in-class collaborative learning exercise, it is suggested that smaller groups were more appropriate. Another supporting research conducted by Rezaei (2018) states that the students need their instructors to communicate with them more often and create rules and procedures for students' communications after class. Moreover, instructors should train students in the basics of teamwork and how to work in groups effectively, and they recommend teachers to be very clear in their expectations for group projects.…”
Section: Group Workmentioning
confidence: 99%
“…In situations where there is a shorter amount of time available to complete a group task, such as an in-class collaborative learning exercise, it is suggested that smaller groups were more appropriate. Another supporting research conducted by Rezaei (2018) states that the students need their instructors to communicate with them more often and create rules and procedures for students' communications after class. Moreover, instructors should train students in the basics of teamwork and how to work in groups effectively, and they recommend teachers to be very clear in their expectations for group projects.…”
Section: Group Workmentioning
confidence: 99%
“…In addition, the other benefit of working in group work is the students will learn to become team players. In his study, Rezaei (2018) found that group work is used to improve the students' teamwork skills. This is based on the opportunity created to get the students to cooperate in completing tasks given.…”
Section: Group Interactionmentioning
confidence: 99%
“…It will also train them to be accountable of the individual parts assigned given to them. Nevertheless, Rezaei (2018) pointed out that even if the students view this as a beneficial to them, they prefer to be evaluated individually for their respective contributions. Hence, this shows that the students view group work as an opportunity to perform as a good team player.…”
Section: Group Interactionmentioning
confidence: 99%
“…Next the study by Chang & Kang (2016) Next, the study by Razaei (2018) was done to investigate what makes group work to be successful. The researcher asked the faculty (instructors and learners) why they gave group work assignments to their students and what their opinions about the best practices in creating effective group work environment for their students are.…”
Section: Past Studiesmentioning
confidence: 99%